Management of diabetic foot ulcers: dermatology perspective - Daryago, Adi Agung Anantawijaya; Fitriani, Fitriani; Kartowigno, Soenarto; Aryani, Inda Astri; Yahya, Yulia Farida; Diba, Sarah; Stephanie, Aurelia (DiscoverSys Inc, 2021)
Diabetes mellitus (DM) is a chronic and complex disease that affects various parts of the body. It can lead to multiple systemic complications and also cutaneous manifestation. Diabetic foot ulcer (DFU) is one of the most devastating complications of DM in dermatology. The main etiology is an increase in plasma glucose, risk factors, or comorbidities due to DM itself.Â Neglected DFU can lead to further complications, including high amputation and mortality rates; thus, the healing of ulcers is the main objective of the treatment. Management is divided into the standard of care and adjuvant therapies. This study aims to optimize DFU management, so it can provide proper treatment and prevent complications.